2006
DOI: 10.1080/01457630600684120
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HIV-1 Replication by a Combination of Endonucleolytic Ribozymes (RNase P and tRNase ZL)

Abstract: We examined the combinatorial action of RNase P and tRNase ZL-mediated specific inhibition of HIV-1 in cultured cells. We designed two short extra guide sequences (sEGS) that specifically recognize the tat and vifregions of HIV-1 mRNA and mediate the subsequent cleavage of hybridized mRNA by the RNase P and tRNase ZL components. We constructed an RNase P and tRNase ZL-associated vif and tat sEGS expression vector; which used the RNA-polymerase III dependent U6 promoter, as an expression cassette for EGS. Toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It has previously been shown that custom-designed EGS molecules could induce human RNase P to cleave HIV RNA sequence in vitro and could inhibit HIV infection in cultured cells [33], [34]. The approach described in the current study, which uses M1GS ribozymes for blocking HIV infection in human cells, is different from the EGS-based strategy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has previously been shown that custom-designed EGS molecules could induce human RNase P to cleave HIV RNA sequence in vitro and could inhibit HIV infection in cultured cells [33], [34]. The approach described in the current study, which uses M1GS ribozymes for blocking HIV infection in human cells, is different from the EGS-based strategy.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, a reduction of 1000 fold in HSV-1 growth and a reduction of 150 fold in HCMV replication were observed in cells that expressed ribozymes derived from the wild type RNase P ribozyme sequence [30], [31]. It has previously been shown that custom-designed EGS molecules could induce human RNase P to cleave HIV RNA sequence in vitro and could inhibit HIV infection in cultured cells [33], [34]. However, it has not been reported whether M1GS ribozymes can block HIV infection in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…RNase P has also been studied as a powerful tool for targeted cleavage directed by external guide sequences [54]. The combination of RNase P and tRNase Z directed cleavage against the same target (HIV-1 RNA) in culture cells results in a more efficient suppression of the HIV-1 mRNA than the suppression obtained using only one of them [55].…”
Section: Model Substrates and Targeted Clea-vagementioning
confidence: 99%
“…32 In a follow-up study, a combination of RNAse P and RNAse Z L EGS were more efficient at reducing HIV-1 replication than EGS alone. 33 The efficacy of these anti-HIV EGS in long-term infectious assays awaits assessment.…”
Section: Ribozymes and Aptamers Continue To Evolve As Therapeuticsmentioning
confidence: 99%